1974
DOI: 10.1111/j.1528-1157.1974.tb04010.x
|View full text |Cite
|
Sign up to set email alerts
|

Benign Epilepsy of Childhood With Rolandic Spikes

Abstract: Summary Twenty‐six cases of “benign epilepsy of childhood” with Rolandic spikes, thoroughly studied clinically and electroencephalographically, were compared with 26 patients with petit mal or petit mal and grand mal seizures. Absences could be detected in a fair number of children with “benign epilepsy.” Rolandic spikes and MU rhythms were found almost exclusively in patients having convulsions, whether focal or generalized. Rolandic spikes associated with MU rhythms and bilaterally synchronous or asynchronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
5

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 5 publications
3
37
0
5
Order By: Relevance
“…The vertical dipole seen in LKS distinguishes it from the centrotemporal spikes seen in benign Rolandic epilepsy, which have a horizontal dipole [Baumgartner et al, 1996;Gregory and Wong, 1984;van der Meij et al, 2001]. In Rolandic epilepsy there is an increase in the centrotemporal spike activity in sleep [Beaumanoir et al, 1974;Blom and Heijbel, 1975;Dalla Bernardina et al, 2002] similar to the increase in electroencephalographic activity found in LKS and ESES. The clinical syndrome is usually benign.…”
Section: Landau-kleffner Syndromementioning
confidence: 67%
See 1 more Smart Citation
“…The vertical dipole seen in LKS distinguishes it from the centrotemporal spikes seen in benign Rolandic epilepsy, which have a horizontal dipole [Baumgartner et al, 1996;Gregory and Wong, 1984;van der Meij et al, 2001]. In Rolandic epilepsy there is an increase in the centrotemporal spike activity in sleep [Beaumanoir et al, 1974;Blom and Heijbel, 1975;Dalla Bernardina et al, 2002] similar to the increase in electroencephalographic activity found in LKS and ESES. The clinical syndrome is usually benign.…”
Section: Landau-kleffner Syndromementioning
confidence: 67%
“…The clinical syndrome is usually benign. There have been isolated case reports of evolution from Rolandic epilepsy to LKS, but it is unclear whether those cases of Rolandic epilepsy were "typical" [Beaumanoir et al, 1974;Cole et al, 1988]. There is some debate as to whether the variability of EEG findings in LKS are due to the variability of the syndrome and the unclear relationship between the EEG abnormalities and the underlying pathophysiology or whether the variability simiply reflects the timing at which recordings were done in relation to the onset of symptoms [Holmes et al, 1981;Tassinari et al, 2002].…”
Section: Landau-kleffner Syndromementioning
confidence: 98%
“…Benign epilepsy with centrotemporal sharp waves (rolandic epilepsy) [7,17,55] The most characteristic manifestations are focal sensomotor seizures, particularly in the cephalic region, as well as unilateral and generalized tonic-clonic attacks. The seizures are usually accompanied by sialorrhoea, and often by speech arrest or dysarthria.…”
Section: Syndromatologymentioning
confidence: 99%
“…In case 1 , generalized spike waves (SWs) appeared during sleep; this has been shown to happen in BECT (Beaumanoir et al, 1974); the same may be said about the occipital spikes noted in case 2 (Beaussart, 1972). In case 1 , generalized spike waves (SWs) appeared during sleep; this has been shown to happen in BECT (Beaumanoir et al, 1974); the same may be said about the occipital spikes noted in case 2 (Beaussart, 1972).…”
Section: Discussionmentioning
confidence: 85%